INFECÇÃO POR Toxoplasma gondii, Neospora caninum, Leishmania major E Trypanosoma cruzi EM CÃES DO ESTADO DO PARÁ - Paz, Giselle Souza Da; Colhado, Bruna Da Silva; Anton, Mariane Martinez; Rocha, Katarine De Souza; Silva, Daniela Barbosa Da; Moraes, Carla Cristina Guimarães De; Lucheis, Simone Baldini; Langoni, Helio (Universidade Federal de Goiás, 2019)
Abstract A serological inquiry was performed to Toxoplasma gondii, Neospora caninum, Leishmania spp. and Trypanosoma cruzi in dogs from the city of Castanhal and Belém, State of Pará, and the association between seropositive animals and factors such as sex, age, access to the streets and provenance of the animals was studied. 269 healthy dogs with different ages, coming from animal shelters, commercial kennels, Zoonosis Control Centre, and domiciles were used. The Indirect immunofluorescence (IIF) reaction was used with plates sensitized with their respective antigens. Among the 263 samples, 100 were reactant, with 38.0% of positivity for Toxplasma gondii, being 16UI and 64UI the prevalent titers, 15.97% of reagent animals for anti-N. caninum antibodies with higher seroprevalence to titers 25UI and 50UI.At the anti-L. major antibodies research, 3.42% were reagent with the titer 40UI being the prevalent. The research of anti-T.cruzi antibodies revealed negativity in all the samples. The provenance and age range variables have been shown as a risk factor to the animals. The animals from the city of Belém presented 2.6 times more changes of infection than the animals from the city of Castanhal. The animals at the age range from three to seven years old presented 2.27 times more changes of being reagent than the dogs with up to three years old. There was no statistical association to the other variables and protozoa researched.

Resumo Realizou-se inquérito sorológico para Toxoplasma gondii, Neospora caninum, Leishmania spp. e Trypanosoma cruzi em cães dos municípios de Castanhal e Belém, no Estado do Pará, e estudou-se a associação entre os animais sororeagentes e fatores como sexo, idade, acesso a rua e procedência dos animais. Foram utilizados 269 cães de diferentes idades, sadios, provenientes de abrigos de animais, canil comercial, Centro de Controle de Zoonoses e domiciliados. Utilizou-se a reação de imunofluorescência indireta (RIFI), com lâminas sensibilizadas de acordo com os seus respectivos antígenos. Das 263 amostras, 100 foram reagentes, com 38,0% de positividade para Toxoplasma gondii, sendo os títulos prevalentes 16UI e 64UI, 15,97% de sororreagentes para anticorpos anti-N. caninum com maior soroprevalência para os títulos 25UI e 50UI. Na pesquisa de anticorpos anti-L. major, 3,42% foram sororreagentes com o título 40UI, sendo o mais prevalente. A pesquisa de anticorpos anti-T. cruzi revelou negatividade em todas as amostras. As variáveis procedência e faixa etária mostraram ser um fator de risco para os animais. Os animais de Belém apresentaram 2,6 vezes mais chances de infecção do que os animais de Castanhal. Os animais na faixa etária de três a sete anos apresentaram 2,27 vezes mais chances de serem sororreagentes do que os cães com até três anos de idade. Não houve associação estatística para as demais variáveis e protozoários pesquisados.
INFECTION BY Toxoplasma gondii, Neospora caninum, Leishmania major AND Trypanosoma cruzi IN DOGS FROM THE STATE OF PARÁ
Keywords: Toxoplasmosis; Leishmaniasis; Neosporosis; Chagas disease; Domestic animals; Toxoplasmose; Leishmaniose; Neosporose; Doença de Chagas; animais domésticos